Konsep Nilai Tukar Uang Perspektif Ekonomi Islam - Sahrani; Nasir, Nur Amaliah; Tauhid, lman (Institut Agama Islam Negeri Parepare, 2022)
This research discusses the transformation of the role of currencies in the context of the global economy and its impact on the Rupiah exchange rate. In the Islamic perspective, fiqh muamalah faces debates regarding currency trading, while Islamic economics emphasizes moral principles and social justice in resource ownership. The literature study outlines the concepts of exchange rates, foreign exchange transactions, and the basics of Islamic economics. The method in this research uses library research, which is a method of collecting data by understanding and studying theories from various literatures related to the research. In Islamic economics, currency exchange activities or exchange rates are called sharf activities. Where the sharf activity is permissible. Sharf is the sale and purchase or exchange between one foreign currency and another foreign currency, such as rupiah with dollars, dollars with yen and so on. The results of the study include the DSN fatwa regarding the interbank money market based on sharia principles, which emphasizes the prohibition of usury and uses contracts such as wadiah, qard, and alsharaf. This study contributes to further understanding of the Islamic view of currency trading in the context of the global economy.